Biofilter Application Using Seaweed (Gracillaria verucosa) to Increase Production of Vannameii Shrimp in Traditional Pond District Bangil-Pasuruan - Sri Andayani; Rani Yuwanita; Nailul Izzah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
The aim of this research to know how to operate and develop the Vannamei production by using biofiter technology of seaweed to the farmer, keeper, young people and leader of the society. The results showed that the Integration of Gracilaria verucosa as a biofilter agent in aquaculture pond can increase the production of Vanname shrimp. The results were obtained 5 tons/ha of seaweed from the initial density of seaweed 1 ton/ha after 3 months of culture with daily growth rate of 4.18%/day. Vannamei shrimp growth of 0.5 grams to 16.7 grams/fish, shrimp production from 1 ton/ha to 3,5 tons/ha. Based on the economic analysis showed gains with the value of R/C ratio of 1.83 and a profitability of 80.08%. Biofilter methods is more likely, given the application is very simple, high adaptability, easy maintenance, and economic value. Socialization and counseling about the application of environmental friendly biofilter system using G. verucosa needs to be carried out at farmer pond.